CLINICAL CHARACTERISTICS AND SHORT-TERM OUTCOMES OF NEONATES WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY TREATED WITH THERAPEUTIC HYPOTHERMIA – SINGLE CENTER EXPERIENCE FROM SERBIA: THERAPEUTIC HYPOTHERMIA IN NEONATES - Biljana, Medjo (Medical Research, 2024)
Aim: This study aimed to report clinical characteristics and short-term outcomes of neonates with hypoxic-ischemic encephalopathy (HIE) managed with hypothermia. Furthermore, we analyzed factors associated with short-term outcomes. Material and Methods: We conducted a single-center retrospective study including neonates with HIE treated with hypothermia who survived hospital discharge. The short-term outcomes were normal or abnormal neurological examination findings at discharge. Results: Forty-five neonates with HIE treated with hypothermia were identified. Median Apgar score at 1 min. was 3 (range 0-7), at 5 min. 5 (range 1-10), while the median blood pH in the first postnatal hour was 6.94 (range 6.8-7.2). On admission, more neonates had moderate than severe encephalopathy according to the modified Sarnat classification (77.8% vs. 22.2%, p<0.001). Twelve (26.7%) neonates presented with complications during hypothermia. The most common complications were coagulopathy presented in 33.3% of cases and arterial hypotension presented in 25% of cases. Twenty-nine (64.44%) neonates had normal neurological examination, whereas 16 (35.56%) presented with abnormal neurological examination findings at discharge (0.006). Twenty-four (53.3%) neonates were discharged from hospital without any therapy. On univariate analysis, abnormal neurological examination findings at discharge were significantly associated with pH < 7 (p=0.009), 5-min Apgar score ≤ 5 (p=0.010), and presence of complications during hypothermia (p=0.013). On multivariate analysis, abnormal neurological examination findings at discharge were significantly associated with pH < 7 (p=0.030) and the presence of complications (p=0.035). Conclusion: Our results during the first, five years of experience with hypothermia support the beneficial effect of hypothermia in neonates with HIE.